Influence of rolling directions on microstructure, mechanical properties and anisotropy of Mg-5Li-1Al-0.5Y alloy - Tianzi Wang; Tianlong Zhu; Jianfeng Sun; Ruizhi Wu; Milin Zhang (Journal of Magnesium and Alloys, 2015)
Mg-5Li-1Al-0.5Y alloy was rolled with different directions. The microstructure, mechanical properties and texture of the specimens were investigated with optical microscope, tensile tester and X-ray diffraction. The results show that changing rolling directions can refine the grain size of as-rolled alloys. Meanwhile, rolling directions have an obvious influence on the mechanical properties and texture of Mg-5Li-1Al-0.5Y alloy, thus affecting the anisotropy of the alloy. The sheet, of which the RD (rolling direction) and ND (normal direction) are both changed between two passes, possesses the smallest anisotropy. From the texture results, changing rolling directions reduces the maximum pole density, making the highest point distribution region excursion and the highest point distributes more scatteredly.